The Structure of San Property Relations: Constitutional Issues and Interventionist Politics - Wilmsen, Edwin N. (Anthropologica, 2022)
Renewed interest in Kalahari San-speaking peoples in the 1950s led to revival of 19th-century concepts of them as nomads without systemic notions of property. Ethnographic and popular literature drew pictures of peoples without fixed ideas about land tenure, as distinct from usufruct rights or personal property, who solved social conflicts by fission of the group. These concepts can no longer be maintained. Nevertheless, transnational organizations have adopted them to challenge current property arrangements, particularly with regard to the Central Kalahari Game Reserve in Botswana, employing a neo-liberal ideology based on their own notion of social justice to justify selection of San peoples as a special target group for empowerment in opposition to other "groups" and in challenge to government policies. In so doing, they create social animosity and increase the economic vulnerability of the targetted people.